Bibliometric Analysis of Value at Risk in Islamic Portfolio: Trends, Gaps, and Future Directions - Yulandri, Elsa; Heryana, Toni; Utama, Wahyudayanto; Nugraha; Waspada, Ikaputera; Purnamasari, Imas (Journal of Islamic Economics and Business, 2024)
This study explores trends, intellectual structures, and thematic evolution in the literature on Value at Risk (VaR) for Islamic portfolios, identifying research gaps and proposing future directions. Using bibliometric analysis, it synthesizes 311 articles from the Scopus database (2005–2025) through Biblioshiny in RStudio and VOSviewer, focusing on publication trends, influential authors, affiliations, and thematic structures. The findings reveal steady growth in VaR literature for Islamic portfolios, with a 3.53% annual growth rate and contributions from 677 authors. Key contributors include Hammoudeh S., Mensi W., and institutions like International Islamic University Malaysia and Prince Sultan University. Thematic analysis highlights advanced methodologies such as GARCH and wavelet analysis, enhancing Islamic finance approaches. Thematic evolution shows a shift from foundational Islamic finance topics to complex analyses of volatility spillovers and dynamic connectedness. The study identifies nine research clusters and recommends integrating ESG considerations, improving risk management, and strengthening portfolio diversification. This research offers valuable insights for practitioners and policymakers in Islamic finance, underscoring the importance of tailored risk assessment tools. It provides a roadmap for scholars to address gaps, particularly in adapting conventional VaR methods to align with Islamic principles. To the authors’ knowledge, this is the first comprehensive bibliometric analysis on VaR in Islamic portfolios, significantly contributing to the literature by mapping intellectual landscapes and offering actionable future research directions.